The Eurozone needs exit rules - Fahrholz, Christian; Wójcik, Cezary (Journal of Banking & Finance, 2013)
This study argues that the key issue for defining and solving the Eurozone’s (EZ) difficulties lies in readjusting the relationship between the centre and the periphery of the EZ. Our argument proceeds in two steps. Firstly, the basic finance problem of a centre-periphery system is captured by a threat game with complete but imperfect information. To get close to the essence of the current EZ sovereign debt crisis we analyse to what extent a ‘troubled’ periphery member can negotiate a bailout from the centre due to the existence of a negative externality arising from its potential default. Secondly, we analyse how establishing ‘exit rules’ would shift the centre-periphery relationship in a way that safeguards the stability of the EZ. We demonstrate that such rules may help limit the scope for brinkmanship whereby fiscal problems in one member state create a negative externality for the rest of the EZ. We then discuss key policy implications concerning financial aspects of the centre-periphery relationship within the EZ.